The effects of incline and level-grade high-intensity interval treadmill training on running economy and muscle power in well-trained distance runners - Ferley, D. D.; Osborn, R. W.; Vukovich, M. D. (The Journal of Strength and Conditioning Research, 2014)
Despite a paucity of evidence, uphill running has been touted as a sport-specific resistance-to-movement training tactic capable of enhancing metabolic, muscular, and neuromuscular processes in distance runners in ways similar to previously established resistance-to-movement training methods, such as heavy and/or explosive strength training and plyometric training. Therefore, the purpose of this investigation included documenting the effects of incline and level-grade interval treadmill training on indices of running economy (RE) (i.e., oxygen consumption [VO2] and blood lactate [BLa] responses of submaximal running) and muscle power. Thirty-two well-trained distance runners (age, 27.4 ± 3.8 years; body mass, 64.8 ± 8.9 kg; height, 173.6 ± 6.4 cm; and VO2max, 60.9 ± 8.5 ml/min/kg) received assignment to an uphill (GHill = 12), level-grade (GFlat = 12), or control (GCon = 8) group. GHill and GFlat completed 12 interval and 12 continuous run sessions over 6 weeks, whereas GCon maintained their normal training. Dependent variables measured before and after training were VO2 and BLa at 2 separate velocities associated with lactate threshold (VLT) (VO2-60% and VO2-80%; and BLa-60% and BLa-80%, respectively); percentage of VO2max at lactate threshold (%VO2max at VLT); muscle power as assessed through a horizontal 5-jump test (5Jmax); and isokinetic knee extension and flexion at 3 angular velocities (90, 180, and 300°/s). Statistical significance was set to p < 0.05. All groups significantly improved 5Jmax, VO2-60%, VO2-80%, BLa-60%, and BLa-80%. Additionally, GHill and GFlat significantly improved %VO2max at VLT. Other indices of RE and muscle power did not improve. We conclude incline treadmill training effective for improving the components of RE, but insufficient as a resistance-to-movement exercise for enhancing muscle power output.